Magnetism and Transport Properties of EuCdBi2 with Bi Square Net - Yi Liu; Jing Li; Shi-Jie Song; Wu-Zhang Yang; Jin-Ke Bao; Wen-He Jiao; Xiao-Feng Xu; Zhi Ren; Guang-Han Cao (Crystals, 2023)
We report a possible coexistence of nontrivial topology and antiferromagnetism in the newly discovered compounds EuCdBi<semantics>2</semantics>, with magnetic Eu layer locating above and below Bi square net. The X-ray diffraction on single crystals and powder indicats that this 112-type material crystalizes in space group of <semantics>I4/mmm</semantics>, the same as SrMnBi<semantics>2</semantics> and EuMnBi<semantics>2</semantics>. Our combined measurements of magnetization, electrical transport and specific heat consistently reveal antiferromagnetic (AFM) transition of Eu<semantics>2+</semantics> moments at <semantics>TN</semantics> = 20 K. The Eu moments are not saturated under a field of 7 T at 1.8 K. The anisotropic susceptibility suggests the Eu moments lie in the <semantics>ab</semantics> plane, and a metamagnetic (MM) transition is observed near 1 T below <semantics>TN</semantics>. Large positive magnetoresistance (MR) present for both <semantics>H ‖ ab</semantics> and <semantics>H ‖ c</semantics>, which are considered to contain part contributions from Dirac bands. Hall measurements show the electron-hole compensation effect is prominent above 100 K, with a crossover of Hall resistance from negative to positive values at ∼150 K. The fitted mobility of electrons is as high as 3250 cm<semantics>2</semantics> V<semantics>−1</semantics> S<semantics>−1</semantics> at 1.8 K. Interestingly, the rapid increase of carrier density and suppression of mobility appear at around <semantics>TN</semantics>, indicating non-negligible interaction between Eu moments and electron/hole bands. EuCdBi<semantics>2</semantics> may provide a new platform to investigate the interplay of topological bands and antiferromagnetic order.